Building Religious Moderation through Theophany Concept with Philosophy and Religion Approaches - Zulkarnaen Zulkarnaen; Adenan Adenan; Marhaban Marhaban; Arief Muammar (Universitas Islam Negeri (UIN) Salatiga, 2023)
This research described an approach to building Religious Moderation according to the Theophany concept, which is an attempt to decide an attitude and action in life through a wise, unbiased perspective, and risk beneficial to many parties. Building religious moderation means forming attitudes and actions to avoid harming oneself, others, and the environment. Furthermore, achieving this process using the Theophany concept enables the formation of attitudes by considering human compassion and contempt, generosity and stinginess, as well as sensitivity and hostility, which are consistently correlated with moral and religious norms. The formation of religious moderation in one's soul brings many benefits to the world. Therefore, it is important to build this concept to determine right from wrong according to certain religious claims. These decisions are based on values, norms, morals, beliefs, and other considerations beneficial for living life. Theophany concept builds the idea that the truth in acting and behaving is God's business as the most righteous judge. In conclusion, building religious moderation is to form a personal soul with moral values beneficial for human life without being free from the justification of certain religious truths.